2008
DOI: 10.1063/1.2938692
|View full text |Cite
|
Sign up to set email alerts
|

Genetic effects of radio-frequency, atmospheric-pressure glow discharges with helium

Abstract: Due to low gas temperatures and high densities of active species, atmospheric-pressure glow discharges ͑APGDs͒ would have potential applications in the fields of plasma-based sterilization, gene mutation, etc. In this letter, the genetic effects of helium radio-frequency APGD plasmas with the plasmid DNA and oligonucleotide as the treated biomaterials are presented. The experimental results show that it is the chemically active species, instead of heat, ultraviolet radiation, intense electric field, and/or cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
112
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 117 publications
(117 citation statements)
references
References 13 publications
3
112
0
Order By: Relevance
“…5 Little is known of the influence that plasma has on DNA. While qualitative work is a good indicator, 9,10 it is vital to quantitatively determine the nature of this influence before any potential application on living tissue can be realized. For applications such as skin treatments and wound healing, it is vital that DNA damage is avoided.…”
mentioning
confidence: 99%
“…5 Little is known of the influence that plasma has on DNA. While qualitative work is a good indicator, 9,10 it is vital to quantitatively determine the nature of this influence before any potential application on living tissue can be realized. For applications such as skin treatments and wound healing, it is vital that DNA damage is avoided.…”
mentioning
confidence: 99%
“…It has been reported that chemically active species formed in the plasma jet during ARTP induce DNA strand breakage. 21) Hence ARTP was used for mutagenesis, by methods described previously. 18−20) Helium gas was used as the plasma-working gas, and the operating parameters were as follows: power input, 115 W; distance between the plasma torch nozzle exit and the sample plate, 2 mm; gas flow rate, 10 L/min; and temperature of the plasma jet, 25-35°C.…”
Section: Methodsmentioning
confidence: 99%
“…Also, some new and powerful mutagenesis methods have been applied to the breeding of high-yielding industrial strains. These new methods have technological advantages (higher mutation rates and more abundant phenotypic mutations) (Hu et al, 2013;Zhang et al, 2015), and include atmospheric and room temperature plasma mutagenesis technology in Beijing (Li et al, 2008;Wang et al, 2010;Lu et al, 2011;Zhang et al, 2014) (Yang et al, 2013), as a type of high linear energy transfer (LET) irradiation, have a higher relative biological effect (RBE) compared with X-and γ-rays (Yang et al, 2007;Li S.W. et al, 2011;Ota et al, 2013;Zhou et al, 2013), and are expected to increase mutation frequency and have a wide mutation spectrum.…”
Section: Introductionmentioning
confidence: 99%